(untitled) (Journal of Global Accounting, 2022)
The study examines the effect of internal control on working capital of Small and medium scale enterprises using University of Benin water factory as a case study. The populations of the study are 70 and were randomly selected based on the availability of the staff meanwhile only 60 were returned by the respondents. Survey design was adopted and primary method of data collection was used. Frequency and percentages was used to analysis the demography data collected while One-Way Monova (Multivariate) was used to test the hypothesis. The result of the analysis shows that internal control has statistical significant effect on payable and internal control has statistical significant effect on receivable of Small and Medium Scale Enterprises in Nigeria. We concluded that internal control is a very vital element of any organization that should not be over looked. We recommended that strong internal control should be put in place by Small and Medium scale Enterprises so as to safe guide their working capital assets and all other asset and proper monitoring should be put in place in order to achieve sustainability of the business..